Sustainable Business Development Via Applying an Online Business Model for Gaining Benefit in Economics, Education, and Social Network - Rochmat Aldy Purnomo; Oksana Malynka; Adi Prananto (EKUILIBRIUM : JURNAL ILMIAH BIDANG ILMU EKONOMI, 2023)
Regional  development  includes  infrastructure  and  information technology.  Infrastructure,  Information  and  Communication Technology  (ICT)  is  worse  in  rural  areas  and  small  towns  in Indonesia. One of such areas is the village of Menowo located in Magelang, Central Java Province, Indonesia. The purpose of this research is to study a contemporary phenomenon of  the Blogger Village within its real-life content. In this research, a case study is described: a young man who was born in the village has started an “online  business  community”.  Now,  people  call  the  Village Menowo “The Blogger Village”. Since 2014, more than 50 people in  the  Blogger  Village  have  got  their  own  revenue  accounts  for hundreds  of  thousands  of  U.S.  dollars  per  month.  The  Blogger Community  has  contributed  to  reducing  unemployment  in  the village.  The  study  has  found  that  the  Blogger  Community  can provide  additional  income  for  Magelang  SMEs.  Magelang  SMEs can use the profit margin of their businesses to update hardware and  software  including  Internet  information  sources  from anywhere.  The  study  provides  new  information  related  to  the regional  development,  local  development,  and  complement economic  empirical  studies  of  a  research  that  has  been  done before.  The  applied  research  is  beneficial  for  the  Government  of Magelang  to  determine  and  develop  policies  of  the  regional economic development of Magelang and to establish appropriate programs  and  activities  for  developing  the  economy  of  the  area. The  research  will  also  help  eliminate  the  overlap  among  the existing  rules  both  at  central  and  local  levels,  as  well  as  among sectors and agencies.